Ali stanje lišajske flore že kaže na spremembo kakovosti zraka v Šaleški dolini po izgradnji čistilnih naprav v termoelektrarni Šoštanj? - Poličnik, Helena (Zbornik gozdarstva in lesarstva, 2007)
Lichens are often used as bioindicators of air pollution due to their biology.Their thallus is without any true tissues and organs, the cuticle and roots are not developed. They get all needed substances from the air. Epiphytic lichens are used (1) for following the heavy metal input into the environment, since they accumulate them, and (2) for the assessment of generalpollution, since they start to decay in polluted areas. In the Šalek Valley area, the input of metals Pb, As, Zn, and Cd into the environment was assessed with the active monitoring method. The epiphytic lichen Hypogymnia physodes was transplanted from reference site (Rogla, Pohorje Mts) to the influential region of the Šoštanj Thermal Power Plant for the period of 6 months. The heavy metal content increased in transplanted lichens in comparison with content in lichens from Rogla. General air pollution was assessed on the basis of present lichen species. Three different methods for mapping epiphytic lichens were used: German (VDI), European (EU) and Slovenian(SI). The assessment of air quality with VDI and EU method is based on presence of different epiphytic lichen species, whereas the air quality assessment according to SI method is based on assessment of frequency and cover of three major thalli types of epiphytic lichens.
Keywords: bioindikacija; lišaji; onesnaženje; Slovenija; Šaleška dolina